(untitled) (The South Asianist Journal, 2015)
(excerpt from the text) In May 2014, to the surprise of many commentators, India’s Bharatiya Janata Party – the BJP – not only won the General Election (as widely expected), but did so with an overall majority by itself, without needing the coalition partners it had attracted before the poll. In the lower House of Parliament – the Lok Sabha – it now has 52% of the seats on 31% of the vote. It is the first time that an avowedly ‘Hindu’ party has held such a dominant position, and even before the election, voices within and outwith India were raised, expressing alarm at the likely impact on inter-religious relations in India. [this essay was first published on September 2nd, 2014 by Discover Society http://www.discoversociety.org, and is here reproduced with permission]